Spirit Filantropi Islam dalam Tindakan Sosial Rasionalitas Nilai Max Weber - Muhammad Erfan (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
Philanthropy is not limited to loving others related to the economic field, such as zakat, infaq, alms, waqf or others. This study aims to inventory the spirit of Islamic philanthropy in Max Weber's social actions, especially in the act of rationality of values from the behavior of the congregation of Majelis Ratib Atthos Palangka Raya. This study is a qualitative study using data collection techniques in the form of observation and documentation. Data analysis was performed using qualitative procedures. The results of this study found the behavior of the assemblies in the form of social actions of value rationality carried out with the spirit of Islamic philanthropy.